Distribution and Contamination Level of Cuprum (Cu) and Plumbum (Pb) in Bulk Sediments of the Bangka Island - Umroh, Umroh; Sari, Suci Puspita; Fabiani, Verry Andre; Ariyanto, Dafit; Siswanto, Aries Dwi; Nuryanto, Nuryanto (Marine Science Department Diponegoro University, 2023)
The distribution and enrichment of heavy metals in sediments will affect the life of the organisms that lives in it. The purpose of this study is to explain the enrichment and contamination levels of heavy metals Cu and Pb in bulk sediments in the northern and southern parts of Bangka Island. This research was conducted in August - September 2019, using a purposive sampling method. Heavy metal analysis using the Inductively Coupled Plasma - Optical Emission Spectroscopy (ICP-OES) instrument. The results showed that the concentration of the heavy metal Pb in the sediment bulk of northern Bangka Island (Kelabat Bay) was higher than that of South Bangka Island. The concentration of heavy metal Cu at 8 (eight) sites is still below the quality standard (18.7 mg.kg-1) even if the heavy metal Pb at stations 3, 4, and 5 in the waters of the northern half of Bangka Island (Kelabat Bay) is reported to have exceeded the quality standard limit (30.2 mg.kg-1). The highest level of enrichment of heavy metal Pb occurs at station 4 with a value of EF_62.88, and is categorized as very high enrichment and a contamination factor (CF) value of 2.24 (medium category). This condition is due to station 4 being located in Kelabat Bay (semi-enclosed area) with unstable water conditions due to the influence of many activities. The results of this study can be used as input for local governments for the management of water areas on Bangka Island.